Classroom Management in the Implementation of Learning Systems in Schools: A Case Study at State Islamic High School - Edo Setiawan; Ulfa Dwi Jayanti; Ranisa Julia (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Effective classroom management plays a crucial role in creating a conducive learning environment, which directly impacts the success of teaching and learning processes. Objective: This study aims to investigate the application of various classroom management strategies in creating a conducive learning environment and supporting the success of the learning process. Method: The study employs a case study design with a qualitative approach, focusing on the MAN Model Kota Bengkulu. Data collection includes in-depth interviews with teachers, classroom observations, and document analysis. Thematic analysis is used to analyze the collected data. Result: The findings reveal that teachers employ various strategies to manage classrooms effectively, such as encouraging student concentration, active participation, and mental preparedness for learning. Additionally, varied teaching methods and discipline are crucial in maintaining a productive learning environment. However, challenges such as limited facilities and technological constraints were also identified. Conclusion: Effective classroom management is essential for creating a positive and productive learning environment. Contribution: This study provides valuable insights into the implementation of classroom management strategies in secondary schools, emphasizing the importance of teacher skills, institutional support, and effective technology integration. The findings offer practical recommendations for improving classroom management and provide a foundation for future research on this topic.